Correlation of Somatostatin Receptor-2 Expression with Gallium-68-DOTA-TATE Uptake in Neuroblastoma Xenograft Models. (8th August 2017) - Zhang, Libo; Vines, Douglass C.; Scollard, Deborah A.; McKee, Trevor; Komal, Teesha; Ganguly, Milan; Do, Trevor; Wu, Bing; Alexander, Natasha; Vali, Reza; Shammas, Amer; Besanger, Travis; et al.
Abstract : Peptide-receptor imaging and therapy with radiolabeled somatostatin analogs such as 68 Ga-DOTA-TATE and 177 Lu-DOTA-TATE have become an effective treatment option for SSTR-positive neuroendocrine tumors. The purpose of this study was to evaluate the correlation of somatostatin receptor-2 (SSTR2) expression with 68 Ga-DOTA-TATE uptake and 177 Lu-DOTA-TATE therapy in neuroblastoma (NB) xenograft models. We demonstrated variable SSTR2 expression profiles in eight NB cell lines. From micro-PET imaging and autoradiography, a higher uptake of 68 Ga-DOTA-TATE was observed in SSTR2 high-expressing NB xenografts (CHLA-15) compared to SSTR2 low-expressing NB xenografts (SK-N-BE(2)). Combined autoradiography-immunohistochemistry revealed histological colocalization of SSTR2 and 68 Ga-DOTA-TATE uptake in CHLA-15 tumors. With a low dose of 177 Lu-DOTA-TATE (20 MBq/animal), tumor growth inhibition was achieved in the CHLA-15 high SSTR2 expressing xenograft model. Although, in vitro, NB cells showed variable expression levels of norepinephrine transporter (NET), a molecular target for 131 I-MIBG therapy, low 123 I-MIBG uptake was observed in all selected NB xenografts. In conclusion, SSTR2 expression levels are associated with 68 Ga-DOTA-TATE uptake and antitumor efficacy of 177 Lu-DOTA-TATE. 68 Ga-DOTA-TATE PET is superior to 123 I-MIBG SPECT imaging in detecting NB tumors in our model. Radiolabeled DOTA-TATE can be used as an agent for NB tumor imaging to potentially discriminate tumors eligible for 177 Lu-DOTA-TATE therapy.